Decision-Making Roles and Workplace Interpersonal Conflict in an Organizational Setting in Mandaue City - Pagatpat, Philip Jun Atty; Polinar, Mark Anthony N. (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The purpose of this study is to investigate how decision-making responsibilities are perceived, as well as how interpersonal conflict is perceived in the workplace. The study used the descriptive-correlational research design and identified respondents in the organization using a purposive sampling technique for data collection. The study employed simple frequency and percentage, weighted mean, the Chi-Square Test of Independence, and the T-test for independent samples to analyze the collected data. The study's findings revealed that employees in the various departments highly perceived the four Mintzberg decision-making roles: entrepreneurial decision-making, disturbance handling, resource allocating, and negotiator decision-making, with entrepreneurial decision-making being the most prevalent among managers and as perceived by the respondents. The results also revealed that interpersonal conflicts at work are unavoidable, particularly in situations of interdependence, disagreement, interference, and negative emotions, with interdependence being the most visible and felt type of interpersonal conflict in the workplace. Additionally, a positive association was found between the respondents' years of employment and the interpersonal conflict at work regarding negative emotions. It was also discovered that there is a significant positive difference in the perception among employees of the manager's decision-making roles and the workplace interpersonal conflict. The study found that employees see interpersonal disputes as subjective but view managers' decision-making as objective. Managers can help resolve these conflicts, boosting productivity and communication among coworkers. While disputes are common, managers must improve policies and decision-making processes to mitigate and resolve conflicts effectively.